THE FUNDAMENTAL PRINCIPLES OF THE ORGANIZATION AND IMPLEMENTATION OF WORK ON MYOPIA PREVENTION IN PRIMARY SCHOOL CHILDREN (EDUCATION IN THE 21ST CENTURY, 2023)
This article presents the fundamental principles of the organization and implementation of work on myopia prevention in primary school children.It is commonly known, that myopia is often observed at school age, when a child does not follow the rules, regulations, and requirements set for the protection of vision and visual work during activities at school and homework preparation. The issue is compounded by the fact that poor lighting is often installed in school educational institutions, supervision over the observance of the correct body position during students' long-term work is not carried out, and breaks are not arranged in the middle of the lesson to alleviate visual exhaustion.The literary data and work experience indicate that the school's role in the overall child development system, especially in the prevention of myopia, is growing immensely (M.I. Zemtsova, 1973; A.N. Gneusheva, 1982; I.L Felfilman, 2004; N.B, Morskaya, 2016; R.N. Azaryan, L.G. Melikyan, 2020). However, non-observance by students of the norms, rules, terms and demands for the proper organization and conduct of visual work and rest of the eyes during the time of study at school leads to the incidence of myopia in students.The practice shows that many primary school teachers often do not have sufficient theoretical and practical skills and abilities to coordinate and conduct the work of preventing myopia in schoolchildren.Therefore, the profound and diversified study of this issue and the development of fundamental principles for the organization and implementation of work on myopia prevention in primary schoolchildren during the day certainly have the theoretical and practical significance and can serve as the basis for long-term maintenance of good vision in children.